2020
DOI: 10.1186/s12891-020-03213-5
|View full text |Cite
|
Sign up to set email alerts
|

Operative versus nonoperative treatment in children with painful rigid flatfoot and talocalcaneal coalition

Abstract: Background: The management of painful rigid flatfoot (RFF) with talocalcaneal coalition (TCC) is controversial. We aimed to compare operative and nonoperative treatment in children with RFF and TCC. Methods: We retrospectively reviewed medical records and radiographs of children with RFF and TTC treated between 2005 and 2015. The nonoperative treatment consisted of manipulation under anesthesia, cast immobilization and shoe insert after cast removal. The operative treatment consisted of combined TCC resection,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Traditional open techniques may prolong hospitalization for wound management and pain control [ 28 ]. An open technique [ 29 , 30 ] is often performed with an incision over the sustentaculum tali, and then, identifying the bridge edge through the talonavicular joint anteriorly and the residual talocalcaneal joint. Finally, the coalition is resected until the articular cartilage is visible.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional open techniques may prolong hospitalization for wound management and pain control [ 28 ]. An open technique [ 29 , 30 ] is often performed with an incision over the sustentaculum tali, and then, identifying the bridge edge through the talonavicular joint anteriorly and the residual talocalcaneal joint. Finally, the coalition is resected until the articular cartilage is visible.…”
Section: Discussionmentioning
confidence: 99%
“…Giannini et al 10 reported resection of TCC and use of a bioabsorbable screw for subtalar arthroereisis (as endorthesis in the subtalar joint) in 12 patients with excellent and good results in 8 (57.1%) and 3 (21.4%) patients respectively. A nonbioabsorbable screw introduced into the talus was used with the aim of obtaining a “calcaneo-stop” effect in association to the TCC resection as described by Di Gennaro et al 8 in 21 patients with statistically significant AOFAS score improvement postoperatively. Knörr et al 16 reported 4 calcaneo-stop procedures simultaneously performed among 15 patients with symptomatic TCC after arthroscopic resection and a hindfoot valgus >20 degrees, with statistically significant increase in AOFAS score to 90.9 postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that patients in the operated group had better outcomes and seven children in the non-operated group required surgery. Only the patients' return to sport and physical activity was more rapid in the group that underwent non-operative treatment [17].…”
Section: Spherus Talus Screwmentioning
confidence: 92%
“…When reviewing the relevant literature and analysing the appropriate study groups for this experiment, we noted that, in the majority of the studies conducted in the field, boys composed more than half of the study group [1,2,22,17,10,23,24,3,4,18,19,12,13,14,20,25,21,26,7,15,8,16,9]. All the subjects were children with flatfoot and heel valgus.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation